Sailors, Slaves, and Immigrants Bondage in the Indian Ocean World, 1750–1914 - Stanziani, A. (Palgrave Series in Indian Ocean World Studies, 2014)
Slaves, convicts, and unfree immigrants have traveled the oceans throughout human history, but the conventional Atlantic World historical paradigm has narrowed our understanding of modernity. This provocative study contrasts the Atlantic conflation of freedom and the sea with the complex relationships in the Indian Ocean in the long 19th century.